Analysis of practice of dividend payments - Харченко, Н. В. (Scientific Progress & Innovations, 2012)
The methods of determination of fund of dividends are investigated. The necessity of realization of analysis of practice of dividend payments is educed. The process of payment of dividends by Ukrainian companies is described. The examples of calculation of fund of dividends are shown after the method of free balance of net profit of the current period, calculation of fund of dividends after the method of total sum of free balance of net profit of the current and retained earnings of past years, calculation of fund of dividends after the method of permanent size of dividends, calculation of fund of dividends after the method of proof increase of dividends in an absolute value, calculation of fund of dividends after the method of proof increase of dividends on a corresponding percent, calculation of fund of dividends after the method of permanent coefficient (interest) of payments, calculation of fund of dividends after the method of permanent and variable part of dividends at forming of variable part of dividend after the increase of absolute value, calculation of fund of dividends after the method of permanent and variable part of dividends at forming of variable part of dividends after an increase on a corresponding interest. The indices of market activity of joint-stock company are analysed.